Role of AT1angiotensin receptor antagonist in pulmonary complications induced by renal ischemia-reperfusion injury in male and female rats - Saeedeh Ahmadi; Samin Nahavandi; Aghdas Dehghani; Seyed Alireza Sobhani; Tuba Abbasi (BMC Nephrology)
Abstract Background Pulmonary complications following renal ischemia-reperfusion injury (IRI) occur in a gender-dependent manner. Moreover, an imbalance in the renin-angiotensin system (RAS) exacerbates both renal and pulmonary diseases. Overactivation of the classical RAS component the angiotensin type 1 receptor (AT1R) and angiotensin II may worsen renal IRI and remote organ damage, with gender-specific differences. This study aims to investigate the effect of renal IR on lung injury across genders. Methods Sixty Wistar rats (30 females, 30 males) were randomly assigned to three groups within each gender: Sham, IR (Isch), and IR with losartan (AT1R antagonist; Isch). Bilateral renal ischemia was induced for 45 min in all groups except the sham group. After 24 h of reperfusion, blood samples were collected for serum analysis, and kidney and lung tissues were harvested for histopathological examination, as well as assessment of malondialdehyde (MDA), and nitrite levels. The left lung was also weighed to evaluate pulmonary edema. Results Renal IR led to notable increases in plasma creatinine, blood urea nitrogen (BUN), MDA levels, and the extent of damage to the kidney and lung tissues in both genders. In female rats, losartan significantly decreased serum BUN (56.87 ± 13.1 vs. 112.9 ± 8.9 in groups Isch L and Isch), attenuated kidney scores (7.6 ± 1.3 vs. 12.8 ± 1.2 in groups Isch L and Isch), and increased renal (0.18 ± 0.02 vs. 0.10 ± 0.01 in groups Isch L and sham) and pulmonary nitrite concentrations (0.37 ± 0.07 vs. 0.22 ± 0.009 in groups Isch L and sham) following IR. On the other hand, serum MDA levels increased significantly in males treated with losartan (2.6 ± 0.11 vs. 3.9 ± 0.4 in groups sham and Isch L). Furthermore, losartan mitigated IR-induced lung injury in females (6.5 ± 0.6 vs. 8.3 ± 0.3 in groups Isch L and Isch), whereas it had no significant effect in males. Conclusions Our findings suggest that AT1R blockade with losartan confers a gender-dependent protective effect. Specifically, losartan may mitigate IR-induced renal and pulmonary damage in females, potentially through modulation of the nitric oxide pathway and attenuation of oxidative stress.